2004
DOI: 10.1097/00043426-200404000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Severe Vitamin B12 Deficiency in an Infant Associated With a Maternal Deficiency and a Strict Vegetarian Diet

Abstract: The authors present a case of severe megaloblastic anemia and neurologic damage due to vitamin B12 deficiency in a 6-month-old infant. The cause of the vitamin deficiency was a maternal dietary deficiency because of a strict vegetarian diet and prolonged breast-feeding. The importance of early recognition of significant maternal vitamin B12 deficiency during pregnancy and lactation in vegetarians is emphasized so that appropriate supplementation can be given and irreversible neurologic damage in the infant pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 10 publications
0
56
0
2
Order By: Relevance
“…[18][19][20] Several studies report severe neurological effects and classical demyelination lesions in infants of mothers on diets that are deficient in vitamin B 12 . [21][22][23] Although this study did not focus on deficient versus non-deficient groups, lower levels of vitamin B 12 could contribute to the changes in autonomic regulation such as an increased heart rate. Furthermore, low vitamin B 12 and folate concentrations are linked to high homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Several studies report severe neurological effects and classical demyelination lesions in infants of mothers on diets that are deficient in vitamin B 12 . [21][22][23] Although this study did not focus on deficient versus non-deficient groups, lower levels of vitamin B 12 could contribute to the changes in autonomic regulation such as an increased heart rate. Furthermore, low vitamin B 12 and folate concentrations are linked to high homocysteine concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In this population, the iron intake from complementary feeds was inadequate, and this appeared to be exacerbated when 12-23-mo-old children continued to breastfeed. Vitamin B-12 deficiency is well recognized in exclusively breastfed infants of vitamin B-12-deficient mothers (46,47). Previous studies in urban Indian toddlers have also shown that vitamin B-12 concentrations are lower, the prevalence of vitamin B-12 deficiency is higher, folate concentrations are higher, and the prevalence of folate deficiency is lower in children who continue to receive breast milk (34).…”
Section: Tablementioning
confidence: 99%
“…B12 insufficiency during lactation may cause anaemia and neurological damage in both the mother and the breast-fed child, as has been reported in vegetarians (Metz, 1970;Michaud et al, 1992;Weiss et al, 2004). If maternal folate stores are insufficient prior to a subsequent conception, the risk of adverse pregnancy outcome such as preterm delivery and birth defects in the following pregnancy is increased (Smits and Essed, 2001).…”
Section: Introductionmentioning
confidence: 95%